Corn Waste Compost: Organic Fertilizer to Anticipate the Scarcity of Chemical Fertilizers and Agricultural Land Damage in Nagari Manggopoh - Armansyah Armansyah; Nurwanita Eka Sari Putri; Netti Herawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
The Nagari Manggopoh is a central area for agricultural product corn, mainly corn for livestock, in Lubuk Basung District, Agam Regency, West Sumatra, Indonesia. The corn kernels produced are sold to animal feed processing factories. However, the corn stalk waste left after harvest is typically burned, leading to land biota damage and air pollution. This community service project aims to raise awareness and demonstrate the process of converting corn plant waste into compost. The project involved socializing, training, and practical demonstrations on composting corn crop waste. These activities have been conducted through counseling sessions, focus group discussions, and hands-on training from June to August 2022. Following the activities, an evaluation was conducted through discussions with the participants. The project's initial result was that ten stakeholders participated in the socialization of using corn crop waste for composting. Additionally, 15 Batang Piarau Jorong Sago farmer group members in Kenagarian Manggopoh have received training and successfully produced compost from corn stalk waste generated from animal feed crops.